Analisis Laporan Realisasi Anggaran Pendapatan dan Belanja Daerah Pemerintah Kota Depok 2021-2024 - Alifia Rahmawati; Muhamad Raihan; Rifky Syah Rezkty Lubis; Siti Syilva Fadia; Zahwa Khairunnisa Asywaq (Kajian Ekonomi dan Akuntansi Terapan, 2026)
This study aims to analyze the financial performance of the Depok City Government based on the Budget Realization Reports (Laporan Realisasi Anggaran/LRA) for the 2021–2024 period. The analysis focuses on evaluating the government's ability to manage Local Own-Source Revenue (Pendapatan Asli Daerah/PAD) and regional expenditures through the measurement of effectiveness and efficiency ratios. Sound regional financial management is an essential element in achieving good governance, transparency, accountability, and sustainable public service delivery. Therefore, assessing the realization of revenue and expenditure budgets is important to determine the extent to which financial targets have been achieved and resources have been utilized efficiently. This research employed a quantitative descriptive method using secondary data obtained from the Budget Realization Reports of the Depok City Government for the period 2021–2024. The data were analyzed using effectiveness and efficiency ratios and interpreted based on regional financial performance assessment criteria. The findings indicate that the effectiveness ratio improved significantly, increasing from 85% in 2021 (fairly effective) to 106% in 2022, 100% in 2023, and 107% in 2024 (highly effective). Meanwhile, the efficiency ratios were 96%, 98%, 104%, and 98%, respectively. These results suggest that regional expenditure management was generally quite efficient, although an inefficient condition occurred in 2023 when expenditure realization exceeded revenue realization. Overall, the financial performance of the Depok City Government demonstrated positive progress in revenue achievement and expenditure management throughout the study period.